1995
DOI: 10.1248/cpb.43.966
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Constituents of Polygala japonica HOUTT. II. Structures of Polygalasaponins XI-XIX.

Abstract: Nine new oleanane-type saponins polygalasaponins XI-XIX were isolated from the aerial part of Polygala japonica. The structures of these compounds were established on basis of spectroscopic and chemical evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…2a ). We then matched these 17 peaks with the accurate mass (MS) and the molecular formula of known compounds isolated from Polygala according to reported literature values 12 13 14 15 16 17 18 19 32 33 34 35 and the “Dictionary of Natural Products” 36 . Finally, the chemical components present in peak 1–4, 6–11 and 15–17 of C5 were identified ( Table 1 and Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2a ). We then matched these 17 peaks with the accurate mass (MS) and the molecular formula of known compounds isolated from Polygala according to reported literature values 12 13 14 15 16 17 18 19 32 33 34 35 and the “Dictionary of Natural Products” 36 . Finally, the chemical components present in peak 1–4, 6–11 and 15–17 of C5 were identified ( Table 1 and Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Radix Polygalae ( RP ) (Yuan Zhi) is a common Chinese herbal medicinal plant prescribed for treatment of forgetfulness 9 , anxiety 10 , insomnia and depression 11 in the Chinese community. The major chemical components of RP include saponins, xanthones, oligosaccharide esters and alkaloids 12 13 14 15 16 17 18 19 . Recent pharmacological studies have reported that RP has the sedative-hypnotic 10 , memory improving 9 , cognitive-enhancing 20 and neuroprotective effects 19 21 22 .…”
mentioning
confidence: 99%
“…P. japonica is a perennial plant that was collected at autumn in the third year of growth. Phytochemical studies on P. japonica have led to the discovery of a number of triterpenoid saponins with different structures [2][3][4][5][6][7][8][9]. Among identified saponins, some bayogenin types from this plant were found to exert significant anti-inflammatory activity by inhibiting carrageenan-induced acute paw edema in mice in our previous studies, and antibacterial activity of bayogenin and medicagenic acid type saponins in other plants was reported [10].…”
Section: Introductionmentioning
confidence: 82%
“…130 The polygalasaponins XI-XIV from Polygala japonica include a new genin named polygalagenin 205. 131 132 Other named oleanane saponins with known genins are listed in Table 1.…”
Section: Quassinoidsmentioning
confidence: 99%